Apakah BUMD Masih Relevan? (Kajian Literatur) - Donal Devi Amdanata; Aulia Rani Annisava; Burhan Burhan (Sharing: Journal of Islamic Economics Management and Business, 2025)
This study aims to reassess the relevance of Regional-Owned Enterprises (BUMD) in supporting regional economic development in Indonesia by examining scientific literature that discusses their position, challenges, and effectiveness within the framework of modern governance and regulatory dynamics. Employing a qualitative literature review approach, this research synthesizes findings from primary sources, including national and international journals, that address legal, managerial, financial, governance, and political aspects of BUMD operations. The findings reveal that the current relevance of BUMD is increasingly questioned due to several critical issues, such as regulatory gaps and ambiguities, weak implementation of good corporate governance principles, limited and often non-professional human resources, high levels of political intervention, and the dualism in legal forms and governance structures between Perseroda and Perumda. Moreover, significant differences in oversight mechanisms between BUMD and state-owned enterprises (BUMN) contribute to greater legal uncertainty, heightened risks of criminalizing managerial decisions, and hindered managerial professionalism. Nevertheless, the potential for strengthening BUMD remains open through regulatory harmonization, enhanced oversight systems, management professionalization, and stricter application of governance standards. This study concludes that the sustainability and relevance of BUMD depend heavily on comprehensive reforms in regulation and governance to ensure that BUMD can effectively function as accountable drivers of regional development.